The dithiolate-bridged diiron hexacarbonyl complex Na2[(μ-SCH2CH2COO)Fe(CO)3]2 as a water-soluble photoCORM - Fan, Wai Yip (2014)
The water-soluble dimercaptopropanoate-bridged diiron hexacarbonyl complex Na2[(μ-SCH2CH2COO)Fe(CO)3]2 has been prepared, and the X-ray crystal structure and infrared, UV–visible, and ESI spectra of the complex have been obtained. The complex is shown to behave as a photoCORM, whereby all six CO ligands are released within 30 min of visible-light irradiation. Gas-phase FTIR spectroscopy has been used to quantify the release of CO into the headspace above the aqueous solution. The resulting product, tentatively assigned to an iron thiolate salt, is also water-soluble. Cell viability studies show that Na2[(μ-SCH2CH2COO)Fe(CO)3]2 is not cytotoxic toward normal epithelial cells.